HCI and Aging: New Directions, New Principles - Knowles, Bran; Singh, Aneesha; Ambe, Aloha Hufana; Brewer, Robin N; Lazar, Amanda; Petrie, Helen; Vines, John; Waycott, Jenny (Extended abstracts on Human factors in computing systems. CHI Conference, 2024)
Concerns regarding the impacts of stereotyped, deficit-based, and problem-oriented approaches to older adult users have propelled HCI to explore new understandings and ways of approaching aging as a subject in recent years. Meanwhile, older adults' relationships with digital technologies are also evolving, driven both by technological advancements and the destabilizing experience of the global pandemic. Now is an important time to take stock of these changes and their significance to the field of HCI and Aging. This workshop attends, therefore, to the need for collective reflection on where the field is now, how we got here, and where it is heading. In addition to highlighting emerging areas requiring research attention, the workshop will produce a snapshot in time to compare with several years hence as the field continues to evolve. The second part of the workshop responds to the need for a clear alternative to deficit based approaches to designing technologies for older adult users. We will pool the collective wisdom of the HCI and Aging community to generate a set of principles to guide research and development toward maximization of benefit and minimization of harm to older adult users/stakeholders.